Biz Mackey, a giant behind the plate : The Story of the Negro League Star And Hall of Fame Catcher - Weschott Rich (Temple University press, 2018)
Before the time of Josh Gibson and Roy Campanella, James Raleigh 'Biz' Mackey was the quintessential catcher in the Negro Leagues.